Error Bound of Periodic Signals in the Hölder Metric - Tikam Singh; Pravin Mahajan (International Journal of Mathematics and Mathematical Sciences)
We obtain two theorems to determine the error bound between input periodic signals and processed output signals, whenever signals belong to 𝐻𝜔-space and as a processor we have taken (𝐶,1)(𝐸,1)-mean and generalized an early result of Lal and Yadav in (2001).